(untitled) (International Journal of Built Environment and Sustainability, 2019)
The changing in climatic conditions is one of the most significant issues in the twenty-first century. The literature suggests various approaches for the understanding of the harmful influences of climate change. Climate change is caused by increases in atmospheric greenhouse gases, deforestation, altering watercourses and human actions with tragic effect on the environment has turned into certainty, as that the procedure may not be over in a short period or medium period. Climate observations showed that climate change occurrence had unfavorable impacts on society and mostly on built environment. The most vulnerable buildings are the historical buildings. The impact of climate change on historical buildings should be studied very carefully to determine the meteorological parameters and changes which are the most critical for the protection of the cultural heritage. Prediction of the effects of climate change on built cultural heritage for the next 100 years is necessary to take every step to protect the historical buildings that are likely to be worst affected by climate change effects. Against this background, this paper reviews the physical and chemical deteriorations of historical buildings and changing energy consumption of historic buildings. The research exposed the risk to lose cultural heritage and rising energy demand in the Northern part of Cyprus as a case study. Structural engineers and architects should consider the dominant forces of climate change to protect the historical buildings but also to construct sustainable, feasible and durable buildings for future projects.